Numerical modelling of in-line and staggered blockages in parallel flowfield channels of PEM fuel cells. (26th January 2017) - Heidary, Hadi; Kermani, Mohammad J.; Prasad, Ajay K.; Advani, Suresh G.; Dabir, Bahram
Abstract: A blockage in the flowfield channel of a PEM fuel cell can enhance mass transfer of reactant gas from the channel into the catalyst layer and improve cell performance. Here, we wish to identify an optimal lay-out for the placement of blockages in the cathode side flow channels of PEM fuel cells. For this purpose, the effects of in-line and staggered blockage configurations within a parallel flowfield are numerically investigated and their fuel cell performance results are compared with those of a baseline parallel flowfield without blockages. A 3D, multiphase, non-isothermal numerical simulation of a single 9-layer counter-flow PEM fuel cell is performed. Results show that the staggered configuration enhances maximum net power by up to 11% over the baseline case, and by 7% when compared to the in-line case. The presence of over-rib-convection in the staggered configuration reduces the pressure drop by 70% when compared to the in-line case which only experiences over-block-convection. Finally, the effect of gas diffusion layer properties is investigated on PEMFC performance enhancement. Results of this numerical study are consistent with the results from our previous experimental study (Heidary et al. (2016)). Highlights: Numerical modeling of employing blockages in the channel of parallel flowfields of PEMFCs. In-line and staggered blockages are investigated and compared with w/o blocks. Blockages vaporize some generated water due to increased species velocity. Blockages cause higher y-direction velocity to produce better heat transfer. Blockages improve performance, with the staggered configuration being better than in-line and baseline cases.